Evaluación del rendimiento de mestizos (línea por variedad) de Maíz Amarillo Duro (Zea Mays l.) en condiciones de Suelo Ácido del fundo Aucaloma - Tuesta López, Fidel (2009)
The present thesis has as title “Evaluation of the Yield of Mestizos (Line for Variety) of Hard Yellow Corn (Zea mays L.) under conditions of floor acid of the I Found Aucaloma” whose objectives were 1) to Identify the best mestizos of hard yellow corn for the formation of a variety of free pollination for conditions of sour floors and 2) to Determine the production cost and the relationship benefits cost of the different treatments. The experiment was executed in the land of the U.N.S.M. -T, I Found Aucaloma located approximately to 15 Km of Tarapoto,Ddistrito of San Asleep, County of you Lick, Department of San Martin; geographically it presents the following ones coordinated: Longitude west: 76° 21 ' and south latitude: 6° 20 ', to 650 m.s.n.m. You evaluates the yield with complementary characteristic biométricas, vegetative, of 19 used treatments, 15 mestizos with crossings of lines for variety and 4 witness, using the D.B.C.R. (Desing Block Completely Randomizado), with three repetitions whose results were analyzed with the test of F and the test of Duncan. The results demonstrated that significant difference existed among the mestizo (line for variety) and witness for all the registered evaluations, in the one that the treatment T6 (LS8-32 x INIA 602) he reached higher yield with 4,28 t/ha; likewise a bigger net utility with S /. 632,46 new suns or a gain of S /. 0,42 new suns, this represented in the relationship benefits cost, considered as a promissory variety, tolerant to sour floors for their high yield and adaptability.